Enhancement of Five Disciplines under Peter Senge’s Approach for Commercial Pilot Based on Knowledge Management - Siricharuanun, Tanapat; Na-Takuatoong, Onjaree; Koraneekit, Prakob (Scholar: Human Sciences, 2018)
The commercial pilot is a person who has duty and responsibility on safety of all passengers and crews. The development of necessary characteristics of commercial pilots becomes the vital issue that all airlines must be aware of and take any action. According to the study, it was found that important characteristics which help commercial pilots to perform duties effectively are five disciplines under Peter Senge’s Approach. As a result, this research focuses on seeking the approach of five disciplines development for commercial pilots based on the approaches of Knowledge Management, Anticipatory Learning and Appreciative Inquiry. The researcher applied the model of enhancement of five disciplines to 17 commercial pilots and spent 62 days for testing. The obtained model consists of six components, which are 1) Airlines core policy, 2) Personnel, 3) Airline data, 4) Knowledge management activity sheet form, 5) Learning and communication tools and 6) Performance development plan. It is comprised of six procedures as follows; 1) Reviewing policy and data, 2) Pursuing visions, 3) Seeking for experience learning, 4) Creatively developing performances, 5) Examining and reflecting alternatives and 6) Maintaining knowledge for airlines.